REFLECTION AND TRANSMISSION BAND STRUCTURES OF A ONE-DIMENSIONAL PERIODIC SYSTEM IN THE PRESENCE OF ABSORPTION - A. Zh. Khachatrian
On the base of the generalized transfer matrix method the problem of electromagnetic wave propagation through an arbitrary periodic one-dimensional absorbing medium is considered. Analytical expressions for transmission and reflection amplitudes are found. The obtained results are applied to a model system represented by a one-dimensional periodic array of alternating layers of vacuum and a metal characterized by the complex frequency-dependent dielectric function. It is shown that in an occupied whole space periodic system a harmonic time wave process cannot exist. Independently of the frequency value, this process always attenuates.
Keywords: Physics; Optics